La grammatica dei clitici portoghesi Aspetti sincronici e diacronici - GORI, BARBARA (Studi e saggi, 2007)
This book represents an attempt to create a "grammar" of the Portuguese clitics, that is to illustrate their rules and particularities, to provide them with a description and to supply - through the exposition and application of a few simple principles - an explanation of the problem of their position in the sentence. Considerable attention has recently been devoted to the Romance clitics, among which the Portuguese occupy a role of undisputed prominence on account of their objectively peculiar nature. This study, based on the observation of the written literary language, analyses the phenomenon through a synchronic, diachronic and comparative approach to European and Brazilian Portuguese. What emerges is the proposal of a typological interpretation of the clitic pronouns, and the Portuguese clitic pronoun system, as a multiform phenomenon that cannot be reduced to a single model.